South Africa's Trade and Growth - Kowalski, Przemyslaw (OECD Publishing, 2009)
This paper examines key trade and trade related issues facing South Africa. It describes South Africa's re-entry into the global trade architecture and its economic growth in the context of its trade performance, as well as the composition and performance of South African exports at the product and sector level in the period from the early 1990s to 2006. The study also assesses South Africa's comparative trade performance based on a gravity model of international trade and discusses some key historical and recent trade policy developments. Finally, the study provides an econometric assessment of the impact of South Africa's trade liberalisation during the period from 1988 to 2003 on labour and total factor productivity across its industrial sectors. It shows that while South African trade performance has been good in recent years there is significant room to liberalise further as an adjunct to labour market reforms. Further trade policy liberalisation would bring about important equity and efficiency gains. Multilateral trade liberalisation has the potential to maximise the gains and ease the transition to freer trade for South Africa but unilateral liberalisation also deserves consideration
Keywords: Trade; South Africa